Mutual efforts for mutual trust: Impacts of citizens' knowledge and governmental communication channels on trust in participatory budgeting - Lee, Junesoo; Kim, Soonhee; Lee, Jooho (Journal of Public Affairs, 2023)
Since participatory budgeting (PB) has been advocated by both theorists and practitioners of public administration, its adoption has become a global phenomenon. As of 2017, all local governments in South Korea are legally mandated to operate a PB system as a policy for inviting citizen participation in local budget decision-making. Using an impact assessment tool completed by PB managers in local governments, this research tested two sets of independent variables—citizens' participatory capacity and the diversification of communication in the PB process—that could be associated with the dependent variables “citizens' trust in government (CTG)” and “government officials' trust in citizens (GTC).” The paper presents the three major findings on the common drivers behind CTG and GTC: (1) citizen participants' knowledge on budget and budgeting process; (2) local government's efforts in gathering citizens' inputs for PB; and (3) the mutual efforts to understand the needs and limitations of both citizens and the local government. The paper concludes by exploring the implications for the design and delivery of effective PB implementation.